Create your own equations or formula for any formula or equation using Universal set of Equality Equations

Constant Equality Equations: x÷y÷x = z÷y÷z and x÷y÷x÷y = z÷y÷z÷y where x,y and z # 0 etc..

In Order to understand the possibility and the uses of the equations do the simple maths and check your answer :

eg:a) 5÷2÷5 = 3÷2÷3

and b) 5÷2÷5÷2=3÷2÷3÷2

One can use it for fun to read the result of another and can answer what is the result of other for a number that thought by the other person. However once constant equality Equations and its formation are understood, any equation or formula of maths, physics, engineering, biology, Chemistry, economics, finance etc.. can be redefined and can be joined to meet the inequalities. Its main uses is overcome the limitation of a formula or equations and remove the assumptions in theory and replace constants, Convert Variable or Variable and Constant into a Natural Constant of the given Equation, derive into new equations , find substitute Equations and/or obtain constant value that can be used with simple proportions for any given variable(sl or constant(s).

The use of this constant equality equation don't limit the interchangeably between other subjects for example a physics formula can be clubbed with a chemistry or biology formula or equations and vice versa.

The Equality Constant equations can be considered as a universal set of tool which can operate even on a single constant or variable. This equations also capable to bring the Gap between the Scalar and Vector Quantity and bring them into equality constant value. Following are the set of Constant Equality Equations where v, x, y and z # 0

1) x÷y÷x = z÷y÷z

1a) x÷y÷x = y÷y÷y = z÷y÷z etc..

1b) x÷x÷x = y÷x÷y = z÷x÷z etc..

1c) x÷z÷x = z÷z÷z = y÷z÷y etc..

2) x÷y÷x÷y = z÷y÷z÷y

2a) x÷y÷x÷y = y÷y÷y÷y = z÷y÷z÷y etc..

2b) x÷x÷x÷x = y÷x÷y÷x = z÷x÷z÷x etc..

2c) x÷z÷x÷z = z÷z÷z÷z = y÷z÷y÷z

etc..

3) x÷xy = z÷zy = (x÷x^2 = x÷y^2 = x÷z^2 = y÷y^2 = y÷x^2 = y÷z^2 = z÷z^2 = z÷y^2 = z÷x^2 ( where x = y, y =z and z=x))

4) xy ÷ x = zy ÷ z = (x^2÷x = y^2÷x = z^2 ÷ x = y^2÷y = x^2 ÷ y = z^2÷y = z^2 ÷ z = y^2÷z = x^2 ÷z ( where x = y, y =z and z=x))

5) x÷xy^2 = z÷zy^2 = ( x÷x^3 = x÷y^3 = x ÷z^3 = y÷y^3 = y÷x^3 = y÷z^3 = z÷z^3 = z÷y^3 = z ÷ x^3 ( where x = y, y =z and z=x))

6) xy^2 ÷ x = zy^2 ÷ z = ( x^3 ÷ x = y^3 ÷ x = z^3 ÷ x = y^3 ÷ y = x^3 ÷ y = z^3 ÷ y = z^3 ÷ z = y^3 ÷z = x^3 ÷ z( where x = y, y =z and z=x))

7) if x÷ xy # z ÷ zv then

(x÷ xy ) * z ÷ zv = x ÷ xy * (z ÷ zv)

((x÷ xy ) * z ÷ zv ) ÷ ((x÷ xy ) * z ÷ zv ) ^ 2 =( x ÷ xy * (z ÷ zv)) ÷ ( x ÷ xy * (z ÷ zv))^2

((x÷ xy ) * z ÷ zv ) ÷ ((x÷ xy ) * z ÷ zv ) ^ 3 =( x ÷ xy * (z ÷ zv)) ÷ ( x ÷ xy * (z ÷ zv))^3

x÷ xy = ( z÷ zv ÷ (z ÷ zv )) * x ÷ xy = ( z÷ zv * (zv ÷ z )) * x ÷ xy etc..

z ÷ zv = ( x÷ xy ÷ (x ÷ xy)) * z ÷ zv = (x÷ xy *(xy ÷ x)) * z ÷ zv etc…

// Same method of double division and triple division can also be applied in all # cases to obtain a Constant Equality Equation equation as shown below :

(x÷ xy ) ÷ ( z ÷ zv) ÷ (x÷ xy) = (z ÷ zv) ÷ ( z ÷ zv) ÷ ( z ÷ zv)

(x÷ xy ) ÷ ( z ÷ zv) ÷ (x÷ xy) ÷ (z ÷ zv) = (z ÷ zv) ÷ ( z ÷ zv) ÷ ( z ÷ zv) ÷(z ÷ zv)

(x÷ xy ) ÷ (x÷ xy) ÷ (x÷ xy) = (z ÷ zv) ÷ (x÷ xy) ÷ ( z ÷ zv)

(x÷ xy ) ÷ (x÷ xy) ÷ (x÷ xy) ÷ (x÷ xy) = (z ÷ zv) ÷ (x÷ xy) ÷ ( z ÷ zv) ÷ (x÷ xy)

8) if x÷ xy # zv ÷ z then

(x÷ xy ) * zv ÷ z = x ÷ xy * (zv ÷ z)

x÷ xy = ( zv÷ zv ÷ (zv ÷ z )) * x ÷ xy = ( zv÷ z * (z ÷ zv )) * x ÷ xy etc...

zv ÷ z = ( x÷ xy ÷ (x ÷ xy)) * zv÷ z = (x÷ xy *(xy ÷ x)) * zv ÷ z etc…

//

9) If xy ÷ x # z ÷ zv then

a ) (xy ÷ x ) * z ÷ zv = xy ÷ x * (z ÷ zv)

b ) xy÷ x = ( z÷ zv ÷ (z ÷ zv )) * xy ÷ x = ( z÷ zv * (zv ÷ z )) * xy ÷ x) etc..

c) z ÷ zv = ( xy ÷ x ÷ (xy ÷ x)) * z ÷ zv = (xy÷ x * (x÷ xy)) * z ÷ zv etc..

//

10) If xy ÷ x # zv ÷ z then

a ) (xy ÷ x ) * zv ÷ z = xy ÷ x * (zv ÷ z)

b ) xy÷ x = ( zv÷ z ÷ (zv ÷ z)) * xy ÷ x = ( z÷ zv * (zv ÷ z )) * xy ÷ x) etc..

c) zv ÷ z = ( xy ÷ x ÷ (xy ÷ x)) * zv ÷ z = (xy÷ x * (x÷ xy)) * zv ÷ z etc..

//

11) if x÷xy^2 # z÷zv^2 then

(x÷xy^2 ) * z÷zv^2 = ( z÷zv^2) * x÷xy^2

(x÷xy^2 ) = ( z÷zv^2 *( zv^2 ÷z )) * x÷xy^2 = z÷zv^2 ÷ ( z ÷ zv^2 )) * x÷xy^2 etc..

z ÷ zv^2 = (x÷xy^2 *( xy^2 ÷ x )) * z÷ zv^2 = (x÷xy^2 ÷ ( x÷ xy^2 )) * z÷ zv^2 etc.

//

12) if x÷xy^2 # zv^2÷z then

(x÷xy^2 ) *zv^2 ÷ z = (zv^2 ÷ z) * x÷xy^2

(x÷xy^2 ) = ( z ÷ zv^2 *( zv^2 ÷z )) * x÷xy^2 = z÷zv^2 ÷ ( z ÷ zv^2 )) * x÷xy^2 etc..

zv^2 ÷ z = (x÷xy^2 *( xy^2 ÷ x )) * zv^2 ÷z = (x÷xy^2 ÷ ( x÷ xy^2 )) * zv^2÷z etc.

//

13) if xy^2÷x # z÷zv^2 then

(xy^2÷x ) * z÷zv^2 = ( z÷zv^2) * xy^2 ÷x

(xy^2÷x ) = ( z÷zv^2 *( zv^2 ÷z )) * xy^2 ÷ x = z÷zv^2 ÷ ( z ÷ zv^2 )) * xy^2 ÷ x etc..

z ÷ zv^2 = (x÷xy^2 *( xy^2 ÷ x )) * z÷ zv^2 = (xy^2 ÷ x ÷ ( xy^2 ÷ x )) * z÷ zv^2 etc.

//

14) if xy^2 ÷ x # zv^2÷z then

(xy^2 ÷ x ) *zv^2 ÷ z = (zv^2 ÷ z) * xy^2 ÷ x

(xy^2 ÷x ) = ( z ÷ zv^2 *( zv^2 ÷z )) * xy^2 ÷ x = z÷zv^2 ÷ ( z ÷ zv^2 )) * xy^2÷x etc..

zv^2 ÷ z = (x÷xy^2 *( xy^2 ÷ x )) * zv^2 ÷z = (xy^2 ÷x ÷ ( xy^2 ÷ x )) * zv^2÷z etc.

//

15) a ) x ÷ (xy^n) = z ÷ (zy^n) = 1 ÷ y^n etc..

b) (xy^n) ÷ x = (zy^n) ÷ z = y^n etc..

**

16) Constant Symmetrical equality model equations :

x ÷ (x^2 * (y^n)^2) * x = z ÷ (z^2 * (y^n)^2) * z = x ÷ (x^2 * (y^n)^2 ÷ x) = z ÷ (z^2 * (y^n)^2 ÷ z) etc..

x ÷ (x^2 * (v(y^n))^2) * x = z ÷ (z^2 * (v(y^n))^2) * z etc...

x^2 ÷ (x^2 * (y^n)^2 ) = z^2 ÷ (z^2 * (y^n)^2 ) = 1 ÷ (y^n)^2 etc….

x^2 ÷ (x^2 * (v(y^n))^2 ) = z^2 ÷ (z^2 * (v(y^n))^2 ) = 1 ÷ (y^n)^2 etc….

(x÷xy)÷v = (z÷zy)÷v etc…

(xy ÷ x)÷v = (zy ÷ z) ÷v etc..

(x÷xy^2) ÷v = (z÷zy^2)÷v etc..

(xy^2 ÷ x)÷v = (zy^2 ÷ z)÷v etc..

x ÷ (xy ÷ 2 + xy ÷ 2) = z ÷ (zy ÷ 2 + zy ÷ 2) etc…

(xy ÷ 2 + xy ÷ 2 ) = zy ÷ z etc..

x÷(xy^2 ÷ 3 + xy^2 ÷ 3 + xy^2 ÷ 3) = z÷zy^2 etc…

(xy^2 ÷ 3 + xy^2 ÷ 3 + xy^2 ÷ 3) ÷ x = (zy^2÷2 + zy^2÷2) ÷ z etc..

18) Constant or Variables replacement models and loops for equations including x = y = z = v = a and # 0 ,:

x = (x÷2 + x ÷ 2) = (x÷ 3 + x ÷ 3 + x ÷ 3) = a(x ÷a) etc.

y = (y÷2 + y ÷ 2) = (y ÷ 3 + y ÷ 3 + y ÷ 3) = a(y ÷a)etc..

z = (z÷2 + z ÷ 2) = (z÷ 3+ z÷ 3 + z ÷ 3) = a(z ÷a) etc..

v = (v ÷3 + v ÷ 3 + v ÷ 3) = (v÷ 4 + v ÷ 4 + v ÷ 4 + v ÷ 4) = a(v ÷a) etc..

a = (a ÷2 + a ÷ 2 ) = (a ÷ 3 + a ÷ 3 + a ÷ 3 ) = a(a ÷a) etc..(one of the easiest loop for unlimited number of equations or formulas through iteration)

xy = (xy ÷ 2 + xy ÷ 2) = (xy ÷ 3 + xy ÷ 3 + xy ÷ 3 ) = a(xy ÷a) = v = (v ÷3 + v ÷ 3 + v ÷ 3) = (v÷ 4 + v ÷ 4 + v ÷ 4 + v ÷ 4) = a(xy ÷a) etc..etc…

zy = (zy ÷ 2 + zy ÷ 2) = (zy ÷ 3 + zy ÷ 3 + zy ÷ 3 ) = a(zy ÷a) etc..

x^2 = y^2 = z^2 = v^2 = (x^2 ÷ 2 + x^2 ÷ 2) = (y^2 ÷ 3 + z^2 ÷ 3 + v^2 ÷ 3 ) = a(x^2 ÷a) = a(y^2 ÷a) = a(z^2 ÷a) = a(v^2 ÷a) etc..(where x = y = z = v)

xy^2 = (xy^2 ÷ 2 + xy^2 ÷ 2 ) = (xy^2 ÷ 3 + xy^2 ÷ 3 + xy^2 ÷ 3 ) = (x ÷ 2 + x ÷ 2)*y^2 = a(xy^2 ÷a) etc..

zy^2 = (zy^2 ÷ 2 + zy^2 ÷ 2 ) = (zy^2 ÷ 3 + zy^2 ÷ 3 + zy^2 ÷ 3 ) = a (z÷a) * a(y^2 ÷a) = a(zy^2 ÷ a ) etc.

zv^2 = (zv^2 ÷ 2 + zv^2 ÷ 2 ) = (zv^2 ÷ 3 + zv^2 ÷ 3 + zv^2 ÷ 3 ) = a (z÷a) * (v^2 ÷ 2 + v^2 ÷ 2) = a(zv^2 ÷ a ) etc.

y^n = (y^n ÷ 2 + y^n ÷ 2 ) = (y^n ÷ 3 + y^n ÷ 3 + y^n ÷ 3 ) = a = a(y^n ÷ a ) etc.

(v(y^n))^2 = ( (v(y^n))^2 ÷ 2 + (v(y^n))^2 ÷ 2 ) = ( (v(y^n))^2 ÷ 3 + (v(y^n))^2 ÷ 3 + (v(y^n))^2 ÷ 3 ) = a( (v(y^n))^2 ÷ a ) etc..

**

x^n ÷ x^ny^n ÷ x^n = z^n ÷ x^ny^n ÷ z^n etc..

x^n ÷ z^ny^n ÷ x^n = z^n ÷ z^ny^n ÷ z^n etc..

x^n ÷ x^ny^n ÷ x^n ÷ x^ny^n = z^n ÷ x^ny^n ÷ z^n ÷ x^ny^n etc..

x^n ÷ z^ny^n ÷ x^n ÷ z^ny^n = z^n ÷ z^ny^n ÷ z^n ÷ z^ny^n etc.

x^n ÷ z^nv^n ÷ x^n = z^n ÷ z^nv^n ÷ z^n etc..

x^n ÷ (z^nv^n)^n ÷ x^n = z^n ÷ (z^nv^n)^n ÷ z^n etc..

x^n ÷ z^nv^n ÷ x^n ÷ z^nv^n = z^n ÷ z^nv^n ÷ z^n ÷ z^nv^n etc..

x^n ÷ (z^nv^n)^n÷ x^n ÷ (z^nv^n)^n = z^n ÷ (z^nv^n)^n ÷ z^n ÷ (z^nv^n)^n etc.

x^n ÷ z^n÷ x^n = z^n ÷ z^n÷ z^n = y^n ÷ z^n÷ y^n etc..

x^n ÷ x^n ÷ x^n = z^n ÷ x^n ÷ z^n = y^n ÷ x^n÷ y^n etc..

y^n ÷ y^n÷ y^n = z^n ÷ y^n÷ z^n = x^n ÷ y^n÷ x^n etc..

x^n ÷ z^n ÷ x^n ÷ z^n = z^n ÷ z^n ÷ z^n ÷z^n = y^n ÷ z^n ÷ y^n ÷z^n netc..

x^n ÷ x^n ÷ x^n ÷ x^n = z^n ÷ x^n ÷ z^n ÷ x^n = y^n ÷ x^n ÷ y^n ÷x^n etc.

y^n ÷ y^n ÷ y^n ÷ y^n = z^n ÷ y^n ÷ z^n ÷ y^n = x^n ÷ y^n ÷ x^n ÷y^n etc..

**

x ÷ xy^n ÷ x = z ÷ xy^n ÷ z etc..

x÷ zy^n ÷ x= z^n ÷ zy^n ÷ z^n etc..

x ÷ xy^n ÷ x ÷ xy^n = z ÷ xy^n ÷ z ÷ xy^n etc..

x ÷ zy^n ÷ x ÷ zy^n = z ÷ zy^n ÷ z ÷ zy^n etc.

19) Conversation and Inverse of y using Constant 1 where x and y # 0:

a) y = 1÷y÷(1÷y)÷(1÷y) = 1÷y÷1÷(1÷y)÷(1÷y) = etc...

b) y = x÷y÷x÷(1÷y)÷(1÷y) = x÷xy * (1÷y)^2 = x÷y÷x÷y÷(1÷y)÷(1÷y) ÷(1÷y)= x÷xy^2* (1÷y)^3 = etc..

Virtually there is no limit in numbers of constant equality equations and values that can be formed, however above can be considered as a standard set that can be used in combination based on value equality. The selection of combination depends on requirement for specific applications or use. Trigonometry functions, Quadratic, Symmetry, Calculus or any other formulas or equations from any subject or combination will fit well within the above constant equality equations and models.

Following is the sample calculation e = mc^2 and e(quantum) = hf

If m = c^2 , h = f and # = not equal

e = c^4 # h^2

e = c^4 *( h^2÷h^2) # h^2 * (c^4 ÷ c^4)

e = c^8 *( h^2) # h^4* (c^4 )

1) e = c^8 *( h^2) ÷ ( h^4* (c^4 ) * c^8 *( h^2)) = h^4* (c^4 )÷ (h^4* (c^4 ) * h^4* (c^4 ))

e = c^8 * h^2 ÷ ( h^6* c^12) = h^4* c^4 ÷ (h^8* c^8 )

You can have many more constant Equality Equations for the above sample calculation of e as per the requirement of applications bridging into total equality.

Observation from the sample calculation is that Constant wave height and fixed wavelength with constant pattern and vibration on fixed velocity may transmit energy from a point to another point without support of any wires and with support of a channel to other dimensions even.

For more samples check the following link:

http://constant9.blogspot.in/2018/03/quantum-meet-relativity-equations.html
History of the equation:

http://constant9.blogspot.in/2016/08/moving-into-any-direction-and-reaching.html

If you want to find constant equality equation for any specific formula and it's observation, you can contact me. Remember knowledge is free but not time.